Damping characteristic identification and damage assessment of a three-storey aluminium frame - Akhila, T.S.; Saji, K.P. (Journal of Structural Engineering, 2024)
Monitoring of the large structural systems for purposes of assessing the potential degradation of structural properties by identifying the dynamic characteristics is needed for assuring the safety of the system. Measurements made at a single point in the structure can be used to detect, locate and quantify the damage. In this work, a method for determining the damping characteristics and identifying the presence, location and severity of structural damage by observing the potential degradation of modal characteristics is presented. This method uses the dynamic properties obtained from the vibration response of the structure both in damaged and undamaged conditions. A three-storied aluminium base frame and 8 damage induced frames were experimentally studied by horizontal shake table. The damage was induced in the base frame by reducing the cross-section of the column. The experimental observations in terms of frequency, displacement and acceleration were used to obtain the dynamic characteristics of the structure. By comparing both theoretical and experimental results of the storey level deflection, the damping ratio of the structure is identified. The identified damping ratio corresponding to each frame is used in the damage assessment algorithm. This algorithm gives reduced storey level stiffness of the structure. The characteristics of the damage in 8 damage induced frames are identified from the results. The method is verified by comparing obtained reduced stiffness with manually calculated stiffness value. The reduction in the stiffness of each storey reflects the location of the damaged column. The analytical results show that the presented method can lead to satisfactory results in most cases.